PUZZLE AKSARA JAWA DARI KARDUS BEKAS SEBAGAI MEDIAINOVATIF PEMBELAJARAN BAHASA JAWA PADA SISWA KELAS IV MINNGLORO, SAPTOSARI, GUNUNGKIDUL - dan Masturoh Delawati S., Amin Nurohmah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research aims to design the innovative Javanese learning media and to improvethe students’ skill of Grade V at MIN Ngloro Saptosari, Gunungkidul in reading theJavanese scripts using the learning media of Javanese scripts puzzle.This research employed the action research designed by Kemmis and Mc. Taggart.The subjects of the research were 21 students of Grade V at MIN Ngloro Saptosari,Gunungkidul. The data collection was done through individual and group test,observation, and interview. The data were analyzed using descriptive qualitative method.The result of the research shows that there is an improvement in the achievementof learning and the students’ appreciation in the teaching and learning process. Thescore of the students Grade V of MIN Ngloro Saptosari, Gunungkidul before implementingthe action was 5. 57 with the highest point 7. 25 while that of after implementing theaction in the first cycle was 6. 52 with the highest point 80. In the second cycle theaverage score improved up to 7.55 with the highest point 90. It can be concluded thatusing puzzle of Javanese scripts can improve the achievement of the students’ learning.Even in the second cycle the percentage of the students’ graduation was 100%. In addition,the students’ attention in the teaching and learning process was better than in the firstcycle which was only 50% and in the second cycle improved 90.48%. The middle criteriain the first cycle were only 34.13%. It improved in the second cycle around 9.52% andlow criteria in the first cycle were 0%.Key words: Puzzle of Javanese Script, the used box, learning media